2020
DOI: 10.1007/s10120-020-01039-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased assessment of HER2 in metastatic gastroesophageal cancer patients: a nationwide population-based cohort study

Abstract: Background Addition of trastuzumab to first-line palliative chemotherapy in gastroesophageal cancer patients with HER2 overexpression has shown to improve survival. Real-world data on HER2 assessment and administration of trastuzumab are lacking. The aim of this study was to assess HER2 testing, trastuzumab administration, and overall survival (OS) in a nationwide cohort of metastatic gastroesophageal cancer patients. Methods Data of patients with synchronous metastatic gastroesophageal adenocarcinoma diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…In recent years, studies in the curative setting showed that oesophagogastric cancer patients treated in high-volume hospitals have a higher chance of receiving treatment, and better outcomes [14,15,21e25]. Our study adds to the increasing body of evidence that this finding also applies in the metastatic setting [13,18]. Clearly, the simple fact that a patient received treatment could explain the improved survival in high-volume centers, as beyond first-line treatment has been shown to improve survival compared to best supportive care [9,10].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In recent years, studies in the curative setting showed that oesophagogastric cancer patients treated in high-volume hospitals have a higher chance of receiving treatment, and better outcomes [14,15,21e25]. Our study adds to the increasing body of evidence that this finding also applies in the metastatic setting [13,18]. Clearly, the simple fact that a patient received treatment could explain the improved survival in high-volume centers, as beyond first-line treatment has been shown to improve survival compared to best supportive care [9,10].…”
Section: Discussionsupporting
confidence: 52%
“…The rise of beyond first-line treatment use could also be a result of a better performance status in patients after first-line treatment as a result of increased efficacy, e.g. due to the rise in the administration of trastuzumab-containing regimens and decrease in monotherapy use [18], or less toxicity in first line, e.g. due to the increase in doublet and decrease in triplet chemotherapy administration [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, to explore whether hospital experience with chemotherapy prescription per se is associated with the outcome indicators, we used a broader treatment experience measure not limited to deceased or palliative patients. For this broader experience measure, the volume of all gastroesophageal cancer patients that received systemic treatment in a curative setting or palliative systemic therapy was calculated, as described earlier [ 16 ]. With the aim to reflect current practice, the volume of recent years (2017 and 2018) was used.…”
Section: Methodsmentioning
confidence: 99%
“…17 It is widely known to all that HER-2 is the most close member related to GC progression. 25 HER-2 is a protooncogene encodes cell-membrane associated proteins erb-b2 receptor tyrosine kinase 2 (ErbB2), which is expressed ubiquitously in all cells and the mutation of this gene is responsible for continuous downstream signaling activation, uncontrolled gene amplification and protein expression in tumor cell, inhibition of programmed cell death, formation of tumor angiogenesis, acceleration of tumor invasion force, weakening the immune system, etc. 26,27 In this context, as a drug target for GC, the relationship between USP8 and HER-2 is worth exploring.…”
Section: Introductionmentioning
confidence: 99%